Evaluation of Gender Differences in Ultrasound Milestone Evaluations During Emergency Medicine Residency Training: A Multicenter Study. Issue 2 (24th October 2019) - Acuña, Josie; Stolz, Uwe; Stolz, Lori A.; Situ‐LaCasse, Elaine H.; Bell, Gregory; Berkeley, Ross P.; Boyd, Jeremy S.; Castle, David; Carmody, Kristin; Fong, Tiffany; Grewal, Ekjot; Jones, Robert; et al.
Abstract: Objectives: Prior literature has demonstrated incongruities among faculty evaluation of male and female residents' procedural competency during residency training. There are no known studies investigating gender differences in the assessment of procedural skills among emergency medicine (EM) residents, such as those required by ultrasound. The objective of this study was to determine if there are significant gender differences in ultrasound milestone evaluations during EM residency training. Methods: We used a stratified, random cluster sample of Accreditation Council for Graduate Medical Education (ACGME) EM residency programs to conduct a longitudinal, retrospective cohort analysis of resident ultrasound milestone evaluation data. Milestone evaluation data were collected from a total of 16 ACGME‐accredited EM residency programs representing a 4‐year period. We stratified milestone data by resident gender, date of evaluation, resident postgraduate year, and cohort (residents with the same starting date). Results: A total of 2, 554 ultrasound milestone evaluations were collected from 1, 187 EM residents (750 men [62.8%] and 444 women [37.1%]) by 104 faculty members during the study period. There was no significant overall difference in mean milestone score between female and male residents [mean difference = 0.01 (95% confidence interval CI = −0.04 to 0.05)]. There were no significant differences between female and male residents' mean milestone scores at the first (baseline) PGY1 evaluation (mean difference = −0.04 [95% CI = −0.09 to 0.003)] or at the final evaluation during PGY3 (mean difference = 0.02 [95% CI = −0.03 to 0.06)]. Conclusions: Despite prior studies suggesting gender bias in the evaluation of procedural competency during residency training, our study indicates that there were no significant gender‐related differences in the ultrasound milestone evaluations among EM residents within training programs throughout the United States.